Education on Occupational Health and Health Related Habits among Dental Students in Croatia - Krešimir Matoš; Zrinka Jurec; Ivan Galić; Marin Vodanović (University of Zagreb. School of Dental Medicine, 2016)
Introduction: Occupational diseases are diseases caused by occupational exposures at the workplace, while diseases related to work are diseases caused by many factors, wherein the harmful work conditions are one of the possible causes. Dental medicine is a profession with a high risk of developing occupational diseases. The aim of this paper was to present the results of a survey about occupational health risks and health related habits among dental students at the School of Dental Medicine University of Zagreb and to show how this survey led to an improvement in education by introducing a new course into the dental curriculum. Participants and methods: Students of all years at the School of Dental Medicine University of Zagreb (total of 663) were offered to participate in a survey about occupational health risks and health related habits. Results: A questionnaire was completed by 351 students. 28.0% of male students and 22.5% of female students were smokers. During the first two years of study, up to 84.6% of students consumed alcoholic beverages at least once a week. Prior to enrollment in the university, 85.3% male and 77.6% female students were engaged in sports. The significant drop in the number of students who participated in sports was noticed in the first study year in both sexes. Student awareness of the health risks related to dental profession increases with the year of study. Most students believe that occupational diseases can be prevented. Conclusion: The results have shown that students enter the School of Dental Medicine with a relatively low level of awareness of the health hazards of dental profession. Although the level of awareness increases with years of study, harmful habits such as smoking, alcohol consumption, and the lack of physical activity also remain present in the later years of study.